Effect of Surface Modification on the Absorption and Luminescence Response in tris(8-Hydroxyquinoline) Gallium Films Achieved by Thermal Treatment - Muhammad, Fahmi Fariq (Journal of Coating Science and Technology, 2015)
This work reports on the impact of surface modification on the optical absorption and luminescence response of vacuum deposited tris(8-hydroxyquinoline) gallium (Gaq3) films. This surface modification was achieved by means of thermal treatment under nitrogen gas in the temperature range from 85 oC to 255 oC. The results of field emission scanning electron microscopy (FESEM) and x-ray diffraction (XRD) technique ascertained the formation of amorphous nano-rods along the surface of Gaq3 films. Considerable improvement in the absorption and luminescence characteristics of Gaq3 films was observed upon surface modification, which has been resulted from this treatment process.